2017
DOI: 10.1007/s13197-017-2868-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fermentation by Ganoderma lucidum and Saccharomyces cerevisiae on rape pollen morphology and its wall

Abstract: This study investigated the mechanism of wall rupture fermentation of the rape bee pollen by and. The enzymatic activities and broken-wall ratios were determined, and the results suggested the involvement of cellulase, protease, and pectinase in the wall rupture fermentation. Among the five substrate inducers, CMCase, protease, and pectinase had the highest enzymatic activities at 23.13 ± 1.09, 63.44 ± 1.35, and 118.61 ± 2.07 U/mL, respectively. The broken-wall ratios of and were 85.08 ± 3.92 and 88.31 ± 2.51%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Bee pollen is composed of pollen collected from angiosperm stamens or gymnosperms by worker bees and mixed with a number of enzymes secreted by nectar and bee salivary glands (such as catalase and amylase) [1]. It contains a variety of essential nutrients such as proteins, carbohydrates, lipids, fatty acids, enzymes and vitamins, as well as flavonoids, alkaloids, and phenolamides [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Bee pollen is composed of pollen collected from angiosperm stamens or gymnosperms by worker bees and mixed with a number of enzymes secreted by nectar and bee salivary glands (such as catalase and amylase) [1]. It contains a variety of essential nutrients such as proteins, carbohydrates, lipids, fatty acids, enzymes and vitamins, as well as flavonoids, alkaloids, and phenolamides [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the enzymes produced by microorganisms could degrade the pollen wall. 10 It was also reported that supercritical CO 2 treatment was effective in breaking the wall of, and extracting functional oil from, rape bee pollen, while a combination of ultrasonication and high shear techniques was employed to disrupt the bee pollen wall and to release nutrients. 9,11 High-pressure processing brought about an increase in carotenoid and phenolic compounds and improvement in the in vitro antioxidant capacity of bee-pollen paste and bee-pollen-based beverage.…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanical, chemical and biotechnological processes have been proposed to enhance the bioavailability of phytonutrients from bee collected pollen. A non-exhaustive list includes: high-shearing [ 8 ], thermal shocks, alone or combined with enzymatic treatment [ 5 ], wet milling [ 9 ], ultrasonication [ 10 ] combined with high-shearing [ 11 ] or enzymatic treatment [ 12 ], chemical extraction of polyphenols with supercritical fluid [ 13 ], fermentation [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%